Evaluation of acrylamide and selected parameters in some Turkish coffee brands from the Turkish market. Issue 4 (3rd April 2019) - Akgün, Banu; Arıcı, Muhammet
ABSTRACT: The purpose of this study was to measure acrylamide (AA) levels and selected parameters of different traditional Turkish coffees. AA, 5-hydroxymethylfurfural (HMF), total reducing sugar, protein, pH, moisture, dry matter (DM) as well as ash, caffeine and soluble solids content (SSC) in DM, L*, a*, b* colour parameters of coffee samples were determined and the correlation between AA level and these parameters were investigated. A total of 36 coffee samples (20 Turkish, 8 Dibek and 8 Terebinth coffee) from the Turkish market were examined. A liquid chromatography-tandem mass spectrometry (LC-MS/MS) method was validated for the detection and quantitation of AA in coffee samples. The calibration curve was linear (R 2  ≥ 0.999) over the range of 30–1000 μg kg −1 . The limit of detection (LOD) and limit of quantification (LOQ) were found as 4.6 μg kg −1 and 15.5 μg kg −1, respectively. The amounts of AA in analysed coffee samples were in the range 31.1 ± 0.6 to 323.4 ± 5.4 µg kg −1 . The highest mean AA levels were found in Terebinth coffees (240.3 μg kg −1 ) followed by Turkish coffees (204.3 µg kg −1 ) and then Dibek coffees (78.6 µg kg −1 ). No tested Turkish coffee samples had an AA concentration above the indicative value (450 µg kg −1 ) for roast coffee recommended by the European Commission (EC) in 2011. In addition, a strong positive correlation was found between HMF values and AA amounts of selected coffee types. GRAPHICAL ABSTRACT: